READING CULTURE AS A BASIS FOR DEVELOPING INNOVATIVE THINKING - Abdulazizov Abdulvokhid Khabibullaevich (Modern American Journals, 2025)
The article describes the author's socio-philosophical point of view on the problems of developing a reading culture, which is considered relevant in modern society, and also attempts to objectively analyze the state of the processes of the role of reading culture, libraries and new information technologies in the development of reading culture among young people. The importance of forming and developing a reading culture among young people is emphasized. Opinions on the importance of reading culture, libraries and new information technologies are presented. At the same time, it is noted that the phenomenon of reading is one of the little-studied areas, and it is concluded that the role of new information technologies as a complex object of research has been little studied, especially in the issue of forming a reading culture of students, recognizing that this phenomenon is very broad and very complex, the role of new information technologies is especially emphasized.
Keywords: political and economic reforms, new stage of library development, reading institutions, electronic documents, attention to reading, new information technologies, electronic means.